Compliance of iron tablets consumption related to anemia status in pregnant women in Cikarang Health Center Bekasi - Fiqriah Ayu Awalamaroh; Leni Sri Rahayu; Indah Yuliana (UHAMKA PRESS, 2018)
Anemia in pregnancy is one of the national problems that reflects the value of the socio-economic welfare of the community which also influences the quality of human resources. Factors that can influence the emergence of anemia among pregnant women include socioeconomic, knowledge, frequency of antenatal care visits, maternal age, distance of pregnancy, parity, infectious diseases, lack of consumption of iron, folic acid, vitamin B12, chronic bleeding, nutritional status, diet, compliance to consume Fe tablets, impaired absorption of iron in the body, and gestational age. The purpose of this study was to determine the association of food sources of Fe consumption, compliance to consume Fe Tablets and knowledge about anemia with anemia status in pregnant women. This research used cross sectional design. The number of samples in this study were 51 pregnant women with gestational age ≥ 36 weeks. Analysis of this research data used Fisher’s Exact. The results of statistical tests showed that there was a significant relationship between compliance to consume Fe tablet adherence to taking Fe tablets (p=0,000) and anemia status in pregnant women gestational age ≥ 36 weeks. Meanwhile, the consumption of Fe (p > 0,05) and knowledge about anemia (p > 0,05) had no significant relationship with anemia status in pregnant women ≥ 36 weeks. Thus, the level of compliance with Fe tablet consumption needs to be maintained and improved. Pregnant women still need to be educated about anemia, the effects and food sources of Fe that should be consumed during pregnancy, so that the level of knowledge can increase. Keywords: Anemia, Compliance of Iron Tablet Consumption, Knowledge, Pregnant Women